Big data analytics enhances agribusines sustainability - Addom, Benjamin K. (Technical Centre for Agricultural and Rural Cooperation, 2018)
Benjamin Addom, ICT4Ag Team Leader at CTA, shares his views on sustainable business models and big data analytics.